Modelling of the expansion phase of Sodium fast reactor severe accident. (15th June 2023) - Mouly, Aude; Seiler, Nathalie; Bertrand, Frédéric; Gradeck, Michel
Abstract: Improving safety is one of the current objective of the fourth generation of sodium fast reactors (SFR). In order to achieve this requirement and increase safety margins, developments are carried-out to take into account severe accidents as soon as the pre-conceptual phase. In this context, fast-running and parametric tools are used in addition to mechanistic tools for parametric studies and probabilistic margin evaluations. This paper is dedicated to MOREINa (Model Of vapouR Expansion and fuel coolant Interaction in sodium fast Reactor), a new parametric tool modelling expansion phase transients. During a severe accident in SFR integrating a low void worth core (non energetic primary phase), a meltdown of the core may occur and form a molten material pool in the vessel. After a secondary power excursion in the molten material pool, the expansion phase implies the self-vaporisation of superheated materials and their expansion towards the sodium located in the upper plenum, above the core. Fuel Coolant Interaction (FCI) will be possible during this phase when the unvaporised overheated molten materials are mixed with the coolant, implying a huge transfer of energy from the superheated materials to the coolant ; vaporising this latter. The mechanical energy released by the two aforementioned phenomena is evaluated during this phase in order to assess the potential damage on the vessel. Thus, MOREINa integrates a new expansion phase model quantifying the mechanical energy induced by this severe accident phase in order to study its consequences on the reactor vessel walls. The modelling implemented in MOREINa, based on dimensional analysis and different balance equations, is able to simulate: - fuel and steel vaporisations; - the creation of a vapour bubble with or without fission gases inside; - the expansion of the molten materials due to the pressure difference between the saturated pressure of the molten materials and the cover gas located above the sodium, at the top of the vessel; - the integration of the molten material droplet into the bubble vapour owing to Rayleigh–Taylor instabilities at the vapour–liquid interface; - the fuel coolant interaction (FCI) if the expansion leads the molten materials to contact the coolant. First, the safety context of the expansion phase study is introduced. The new parametric tool MOREINa is then presented with its main models. Validations of MOREINa against a validated tool and on available test cases are carried-out and, finally, a parametric study is presented and analysed.